The High-Mobility-Group Domain Transcription Factor Rop1 Is a Direct Regulator of prf1 in Ustilago maydis - Brefort, Thomas (American Society for Microbiology, 2005)
In the smut fungus Ustilago maydis, the pheromone signal is transmitted via a mitogen-activated protein kinase module to the high-mobility-group (HMG) domain transcription factor Prf1, leading to its activation. This triggers sexual and pathogenic development since Prf1 binds to the PRE boxes located in the promoters of the a and b mating type genes. Here, we present the characterization of rop1 and hmg3, encoding two additional sequence-specific HMG domain proteins. While hmg3 mutants are slightly impaired in mating and do form conjugation hyphae, rop1 deletion strains display a severe mating and filamentation defect and do not respond to pheromone stimulation. In particular, rop1 is essential for pheromone-induced gene expression in axenic culture. Constitutive expression of prf1 fully complements the mating defect of rop1 mutants, indicating that rop1 is required for prf1 gene expression. Indeed, we could show that Rop1 binds directly to specific elements in the prf1 promoter. Surprisingly, on the plant surface, rop1 deletion strains do form conjugation hyphae and express sufficient amounts of prf1 to cause full pathogenicity. This indicates the involvement of additional components in the regulation of prf1 gene expression during pathogenic growth.